Radicalized - Swantesson, Klara (Sweden : Geffenblad, Uzi, 2006)
An animated short about a 57 year old woman who, after 33 years of working as a teacher, is "burnt out" by a life of modern stress.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films